On the motion of Gyroscop - Huyen, Pham; Mau, Nguyen Thanh (Vietnam Journal of Mechanics, 1993)
In this work the authors had studied the motion of Gyro in mobile basis. Introducing the uncountable by degree units the differential equation system is coming to the stand art form, which can be solver by the method of separation motion. Computed result is the exponential function.